2013
DOI: 10.1111/1462-2920.12329
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic constraints on elemental stoichiometry and resource allocation in heterotrophic marine bacteria

Abstract: Summary The objective of this study was to evaluate the contribution of evolutionary history to variation in the biomass stoichiometry and underlying biochemical allocation patterns of heterotrophic marine bacteria. We hypothesized that phylogeny significantly constrains biochemical allocation strategy and elemental composition among taxa of heterotrophic marine bacteria. Using a ‘common‐garden’ experimental design, we detected significant interspecific variation in stoichiometry, macromolecule allocation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 102 publications
(134 reference statements)
10
74
0
Order By: Relevance
“…Cells were lysed with a bead-beater containing 1 ml of a mixed solution containing one part RNA preservation solution (20 mM ethylenediaminetetraacetic acid; 25 mM sodium citrate; and saturated with ammonium sulfate) and four parts 5 mM Tris buffer. Nucleic acids were measured in the supernatant with the Qubit dsDNA HS Assay Kit and the Qubit HS RNA Assay Kit (Invitrogen, Eugene, OR, USA) according to the method described by Zimmerman et al (2014). This technique provides a linear signal in response to the amount of cell material analyzed and is able to recover nearly 100% of material from standards (from Qubit HS Assay Kit) that were spiked into the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed with a bead-beater containing 1 ml of a mixed solution containing one part RNA preservation solution (20 mM ethylenediaminetetraacetic acid; 25 mM sodium citrate; and saturated with ammonium sulfate) and four parts 5 mM Tris buffer. Nucleic acids were measured in the supernatant with the Qubit dsDNA HS Assay Kit and the Qubit HS RNA Assay Kit (Invitrogen, Eugene, OR, USA) according to the method described by Zimmerman et al (2014). This technique provides a linear signal in response to the amount of cell material analyzed and is able to recover nearly 100% of material from standards (from Qubit HS Assay Kit) that were spiked into the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Initial phytoplankton C, N, P are calculated from (averaged) observed POC, PON, POP concentrations (Franz et al, 2012b(Franz et al, , 2013aHauss et al, 2012), from which we subtract the (averaged) observed dinoflagellate, ciliate, and bacterial biomasses multiplied with assumed zooplankton and bacterial N:C and P:C ratios, Q Table 1. We apply the same N:C and P:C ratios to bacteria (Chrzanowski and Grover, 2008;Pahlow et al, 2008;Zimmerman et al, 2014), which are only used for the calculation of the initial phytoplankton C, N, P in this study. Thus, our initial phytoplankton PON and POP concentrations vary slightly between the different simulations of the same mesocosms, FIGURE 1 | Experimental set-up of the PU1 and PU2 experiments during the M77/3 cruise.…”
Section: Model Setupmentioning
confidence: 99%
“…Marine plankton have taxon-specific limitations on biomass stoichiometry and can have different stoichiometric composition under the same environmental conditions (Grob et al, 2013;Quigg et al, 2003Quigg et al, , 2011Zimmerman et al, 2013). Consequently, community composition affects community stoichiometry, and may contribute to significant differences between oceanic regions Weber and Deutsch, 2010).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Seawater RNA and DNA concentrations were determined using high-sensitivity, macromolecule-specific Quant-iT fluorophores (Molecular Probes, Inc., Eugene, OR, USA) following a crude lysis as previously described (Zimmerman et al, 2013). Briefly, nucleic acids and proteins were released from filters by mechanical lysis (MP FastPrep-24 bead beater, MP Biomedicals, Solon, OH, USA) in a solution of Tris buffer (5 mM) and RNA preservative (saturated ammonium sulfate solution).…”
Section: Nucleic Acidsmentioning
confidence: 99%